2011
DOI: 10.1080/10670564.2011.565179
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Democracy Debate in Hong Kong

Abstract: This article examines the discourses of democracy in the context of political development in Hong Kong during the first 12 years after the 1997 handover using rhetoric and frame analysis. Overall, the study shows how political actors define political options and promote development, which is favourable to their interests and views, through framing democracy in different ways. The study reveals the frames that describe different points of view, and contributes to the understanding of democrats' position as re-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…One of the most salient electoral cleavages in Hong Kong's legislative elections is political liberalization (Oksanen, 2011). In times of elections, pandemocratic candidates frequently exploit this cleavage by urging the government to implement universal suffrage in the election of the Chief Executive and to abolish the functional constituencies, while criticizing the proestablishment camp as a hurdle to democratization.…”
Section: Channel 3: Utilize Pro-establishment Parties' Comparative Admentioning
confidence: 99%
“…One of the most salient electoral cleavages in Hong Kong's legislative elections is political liberalization (Oksanen, 2011). In times of elections, pandemocratic candidates frequently exploit this cleavage by urging the government to implement universal suffrage in the election of the Chief Executive and to abolish the functional constituencies, while criticizing the proestablishment camp as a hurdle to democratization.…”
Section: Channel 3: Utilize Pro-establishment Parties' Comparative Admentioning
confidence: 99%
“…In contrast, the pro-democracy camp (or opposition parties) takes a more progressive stance towards democratisation, advocating an immediate and thorough political reform that endorses the highest degree of autonomy (Oksansen, 2011). The Democratic Party (DP), the Civic Party (CP), the Labour Party, the League of Social Democrats (LSD) and People Power (PP) form part of this camp.…”
Section: Political Parties In Hong Kongmentioning
confidence: 98%
“…The pro-establishment camp, also called pro-Beijing, pro-government or the conservative camp, adopts a more conservative ideology towards democratisation, supporting a gradual and incremental reform process (Oksansen, 2011). Parties belonging to this camp often align with the incumbent HKSAR administration and the Chinese Central Government.…”
Section: Political Parties In Hong Kongmentioning
confidence: 99%
“…In addition, the socialization thesis suggests that political attitudes are transmitted to students through social learning processes (Dunn, 2011). Because tertiary education is westernized and liberal in Hong Kong (Curry, 2012;Mok & Cheung, 2011) and Hong Kong society is generally liberal (Ma, 2011;Oksanen, 2011), tertiary education may tend to predispose university graduates to more left-wing political attitudes (Hastie, 2007;Weakliem, 2002). Consistent with the socialization thesis, the current study found that relative to respondents with secondary education level, respondents with tertiary education level demonstrated lower odds of perceived Lower perceived threat of protestors to the economy was found in unmarried respondents in the current study.…”
Section: Discussionmentioning
confidence: 99%